FINEMET type alloy without Si: Structural and magnetic properties - Muraca, Diego (2008)
Magnetic and structural properties of a Finemet type alloy (Fe73.5Ge15.5Nb3B7Cu1) without Si and high Ge content were studied. Amorphous material was obtained by the melt spinning technique and was heat treated at different temperatures for 1 h under high vacuum to induce the nanocrystallization of the sample. The softest magnetic properties were obtained between 673 and 873 K. The role of Ge on the ferromagnetic paramagnetic transition of the as-quenched alloys and its influence on the crystallization process were studied using a calorimetric technique. Mössbauer spectroscopy was employed in the nanocrystallized alloy annealed at 823 K to obtain the composition of the nanocrystals and the amorphous phase fraction. Using this data and magnetic measurements of the as-quenched alloy, the magnetic contribution of nanocrystals to the alloy annealed at 823 K was estimated via a linear model.